Properties of concrete with the Personal Protective Equipment (PPE) waste / Muhammad Firman Hakim Abdul Halim and Wan Nur Syazwani Wan Mohammad - Abdul Halim, Muhammad Firman Hakim; Wan Mohammad, Wan Nur Syazwani (2023)
A large amount of Personal Protective Equipment (PPE) has been used and subsequently discarded, resulting in an ecological impact during the COVID-19 era. The PPE, being made from plastic, will not decompose for hundreds of years, potentially leading to a global health crisis. As a result, this crisis could affect the world’s population, economy, and overall sustainability. This study aims to: 1) explore the reuse of PPE by incorporating it with concrete and investigate its mechanical properties (i.e., compressive strength, quality of concrete, and water absorption), 2) demonstrate the performance of PPE concrete, and 3) determine the marketability prospect of PPE concrete. A series of experiments were conducted, including a compressive test, ultrasonic pulse velocity test at various curing times (7, 14, and 28 days), and water absorption test (28 days).